Solid electrolyte, preparation method thereof and solid-state battery

By boosting and holding the precursor material during the secondary sintering process, the problems of low conductivity and complex process of NASICON solid electrolyte are solved, and solid electrolytes with high density and ionic conductivity are prepared.

CN119706846APending Publication Date: 2025-03-28XIANGHE KUNLUN NEW ENERGY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411848101.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing preparation method of NASICON type solid electrolyte has problems of low conductivity and complex process, and it is difficult to prepare a solid electrolyte with high ionic conductivity.

Method used

During the secondary sintering process, the precursor material is boosted and then kept in pressure to obtain a solid electrolyte with a short grain boundary distance and a moderate grain size, which reduces the pores inside the solid electrolyte and improves its density and ionic conductivity.

Benefits of technology

The solid electrolyte prepared by this method is denser and the ionic conductivity is significantly improved, which solves the problems of low conductivity and complex process in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005189807840000171
    Figure BDA0005189807840000171
  • Figure BDA0005189807840000181
    Figure BDA0005189807840000181
Patent Text Reader

Abstract

The invention provides a solid electrolyte, a preparation method thereof and a solid-state battery, and the preparation method comprises the following steps: carrying out primary sintering on a mixture of solid electrolyte raw materials to obtain a precursor material, and carrying out secondary sintering on the obtained precursor material to obtain the solid electrolyte, the secondary sintering process comprises the step of pressurizing the precursor material, and the pressurizing step comprises the step of increasing the pressure to 30-45 MPa at the pressure increasing rate of 2-3 MPa / h and then maintaining the pressure. According to the preparation method disclosed by the invention, the precursor material is firstly boosted and then is subjected to pressure maintaining in the secondary sintering process, so that the solid electrolyte with higher density is obtained, and the ionic conductivity of the solid electrolyte is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes and relates to a method for preparing a solid electrolyte, and in particular to a solid electrolyte and a preparation method thereof and a solid-state battery. Background Art

[0002] NASICON solid electrolytes not only have the advantages of high thermal stability, good ion conductivity and wide potential window, but also have certain stability in chemical properties. In addition, NASICON solid electrolytes have a relatively high calcination density, no pollution to the environment, and controllable process conditions, so they are gradually becoming one of the important materials for all-solid power batteries.

[0003] The preparation method of NASICON type solid electrolyte disclosed in the prior art mainly adopts a solid phase method to perform a single sintering, or to prepare a composite electrolyte by adding other substances, so as to improve the ionic conductivity of the electrolyte. However, the above methods have the disadvantages of low conductivity or complicated material preparation process.

[0004] CN105762414A discloses an improved sol-gel method for preparing NASICON type ion-doped lithium germanium phosphate solid electrolyte, which specifically comprises the following steps: firstly dissolving lithium salt, doping ion metal salt and phosphate in deionized water in a stoichiometric ratio and uniformly mixing; preparing a citric acid aqueous solution, adding it to the above salt solution in a certain ratio, and continuing to stir; slowly adding stoichiometric germanium methanol to the above mixed solution; adjusting the pH value of the solution, heating at 50-120°C to generate a complex reaction to obtain a sol; continuing to react the gel at 120-200°C to form a dry gel; grinding the dry gel into powder, and obtaining a precursor after heat treatment at 300-700°C; grinding the precursor a second time, pressing it into a green blank, and calcining it at 800-1000°C to obtain the NASICON type ion-doped lithium germanium phosphate solid electrolyte.

[0005] CN117747956A discloses an inorganic solid electrolyte interface modification method and its application, belonging to the field of lithium battery application technology. The modification method uses polyethylene oxide, lithium salt and filler to configure a uniformly dispersed mixed solution, and uses the mixed solution to modify the surface of the inorganic solid electrolyte to obtain an inorganic solid electrolyte that is stable to lithium. Among them, the addition of fillers can reduce the transmission barrier of lithium ions in the modified layer and improve the lithium ion conductivity of the modified layer; it can also effectively improve the Young's modulus of the interface modification layer and improve its ability to inhibit the growth of lithium dendrites; and reduce its surface potential to reduce the space charge layer effect and promote the uniform deposition of lithium ions. Under the combined effect of the above factors, the lithium stability of the inorganic solid electrolyte is significantly improved.

[0006] The preparation methods of solid electrolytes disclosed in the prior art all have certain defects, such as difficulty in preparing solid electrolytes with high ionic conductivity and complex preparation processes. Therefore, it is very important to develop and design a new type of solid electrolyte and its preparation method and solid-state battery. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a solid electrolyte, a preparation method thereof and a solid-state battery. The preparation method of the present invention obtains a solid electrolyte with a short grain boundary distance and a moderate grain size by first increasing the pressure of the precursor material and then maintaining the pressure during the secondary sintering process, and effectively reduces the pores generated inside the solid electrolyte, thereby making the solid electrolyte denser and improving the ionic conductivity of the solid electrolyte.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a solid electrolyte, the preparation method comprising:

[0010] The mixture of solid electrolyte raw materials is subjected to primary sintering to obtain a precursor material, and the obtained precursor material is subjected to secondary sintering to obtain a solid electrolyte;

[0011] The secondary sintering process includes pressurizing the precursor material, and the pressurization includes increasing the pressure to 30MPa-45MPa at a pressure increase rate of 2MPa / h-3MPa / h and then maintaining the pressure.

[0012] The pressurization described in the present invention includes increasing the pressure at a pressure increase rate of 2MPa / h to 3MPa / h. The pressure increase rate can be, for example, 2MPa / h, 2.1MPa / h, 2.2MPa / h, 2.3MPa / h, 2.4MPa / h, 2.5MPa / h, 2.6MPa / h, 2.7MPa / h, 2.8MPa / h, 2.9MPa / h or 3MPa / h. When the pressure increase rate is too slow, the conductivity of the solid electrolyte will become low. This is because the pressure increase rate is too slow, resulting in poor contact between particles during the sintering process, resulting in insufficient reaction; when the pressure increase rate is too fast, the conductivity of the solid electrolyte will become low. This is because the electrolyte sheet is not pressed evenly enough, resulting in low density.

[0013] The pressurization described in the present invention includes maintaining the pressure after increasing the pressure to 30MPa-45MPa. The maintaining pressure can be, for example, 30MPaMPa, 32MPaMPa, 34MPaMPa, 36MPaMPa, 38MPaMPa, 40MPaMPa, 42MPaMPa, 44MPaMPa or 45MPaMPa, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable. The terminal pressure of the pressurization described in the present invention, that is, the maintaining pressure, will affect the performance of the prepared solid electrolyte. When the maintaining pressure is too low, the conductivity of the solid electrolyte will be reduced, because the density of the fired electrolyte sheet is not enough due to the low pressure. When the maintaining pressure is too high, the conductivity of the solid electrolyte will be reduced, because the abnormal growth of the grains will occur due to the excessively long maintaining time.

[0014] First, since the performance of the solid electrolyte (such as ionic conductivity) mainly depends on the size of the grain growth and the distance between the grain boundaries, and the slow growth of the grains occurs during the secondary sintering process; therefore, in the present invention, the precursor material is first pressurized and then maintained during the secondary sintering process, that is, the pressure is first increased and then maintained during the slow growth of the grains, thereby obtaining a solid electrolyte with a short grain boundary distance and a moderate grain size; secondly, during the preparation process of the solid electrolyte, due to the influence of impurities or moisture in the raw materials themselves, gas volatilization will occur inside the precursor material during the secondary sintering, thereby causing pores to be generated inside the solid electrolyte. In the present invention, the precursor material is first pressurized and then maintained during the secondary sintering process, thereby effectively reducing the pores generated inside the obtained solid electrolyte; therefore, the solid electrolyte prepared by the preparation method provided in the present application is more dense and the ionic conductivity is also improved accordingly.

[0015] The preparation method of the present invention obtains a solid electrolyte with a short grain boundary distance and a moderate grain size by first increasing the pressure of the precursor material and then maintaining the pressure during the secondary sintering process, and effectively reduces the pores generated inside the solid electrolyte, thereby making the solid electrolyte denser and improving the ionic conductivity of the solid electrolyte.

[0016] Preferably, the solid electrolyte raw material includes an inorganic salt and an oxide.

[0017] The mass ratio of the inorganic salt to the oxide in the solid electrolyte raw material of the present invention is not limited, and the mass ratio can be selected according to actual needs.

[0018] Preferably, the inorganic salt includes any one of sodium carbonate, sodium bicarbonate, ammonium hydrogen phosphate or ammonium dihydrogen phosphate, or a combination of at least two thereof; the oxide includes any one of phosphorus pentoxide, phosphorus trioxide, zirconium dioxide or silicon dioxide, or a combination of at least two thereof.

[0019] The inorganic salt in the present invention includes any one of sodium carbonate, sodium bicarbonate, ammonium hydrogen phosphate or diammonium phosphate, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of sodium carbonate and sodium bicarbonate, a combination of ammonium hydrogen phosphate and diammonium phosphate, a combination of sodium carbonate, sodium bicarbonate and ammonium hydrogen phosphate, or a combination of sodium bicarbonate, ammonium hydrogen phosphate and diammonium phosphate.

[0020] The oxides described in the present invention include any one of phosphorus pentoxide, phosphorus trioxide, zirconium dioxide or silicon dioxide, or a combination of at least two of them. Typical but non-limiting combinations include a combination of phosphorus pentoxide and phosphorus trioxide, a combination of phosphorus trioxide and zirconium dioxide, a combination of zirconium dioxide and silicon dioxide, or a combination of phosphorus pentoxide, phosphorus trioxide and zirconium dioxide.

[0021] Preferably, the method of preparing the mixture comprises mixing the solid electrolyte raw materials by dry ball milling.

[0022] Preferably, the rotation speed of the dry ball mill is 200 r / min to 500 r / min, for example, it can be 200 r / min, 220 r / min, 0 r / min, 250 r / min, 270 r / min, 300 r / min, 320 r / min, 350 r / min, 370 r / min, 400 r / min, 420 r / min, 450 r / min or 500 r / min, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 300 r / min to 480 r / min.

[0023] In the present invention, the rate of dry ball milling is limited and regulated so that the raw materials are mixed more evenly, thereby facilitating the subsequent sintering process; when the dry ball milling rate is too low, the raw materials will be mixed unevenly, resulting in more impurities in the reaction products; conversely, when the dry ball milling rate is too high, the powder material will be compacted at the bottom of the ball mill due to the high rotation speed, resulting in uneven mixing of the raw materials.

[0024] Preferably, the dry ball milling time is 30 min to 1800 min, for example, it can be 30 min, 50 min, 100 min, 200 min, 300 min, 500 min, 700 min, 1000 min, 1300 min, 1500 min or 1800 min, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 120 min to 1500 min.

[0025] In the present invention, the dry ball milling time needs to be regulated according to the amount of material, so that the particle size of the raw material is finer and the mixing is more uniform; when the dry ball milling time is too short, the particle size of the obtained mixture will not be fine enough and the mixing will be uneven; conversely, when the dry ball milling time is too long, the conductivity of the solid electrolyte will be reduced. This is because the ball milling tank and the ball milling beads will wear and fall off due to the long time, thereby contaminating the sample.

[0026] Preferably, the forward rotation and the reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.1h to 1h, and the time of each reverse rotation is independently 0.1h to 1h; each time the forward rotation and the reverse rotation are alternately stopped for 5min to 15min, preferably 5min to 10min.

[0027] The present invention adopts a method of alternating forward and reverse rotation, and stops each time the forward rotation switches to the reverse rotation or each time the reverse rotation switches to the forward rotation, thereby achieving heat dissipation during the dry ball milling process, thereby avoiding excessive temperature of the material during the dry ball milling process, thereby avoiding side reactions between solid electrolyte raw materials caused by excessive temperature.

[0028] In the present invention, the time of each forward rotation is independently 0.1h to 1h, for example, it can be 0.1h, 0.2h, 0.4h, 0.6h, 0.8h or 1h, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] In the present invention, the time of each reversal is independently 0.1h~h, for example, it can be 0.1h, 0.2h, 0.4h, 0.6h, 0.8h or 1h, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In the present invention, each time the forward rotation and the reverse rotation alternate, the rotation stops for 5 minutes to 15 minutes, for example, it can be 5 minutes, 7 minutes, 9 minutes, 10 minutes, 11 minutes, 11 minutes or 15 minutes, but it is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable, preferably 5 minutes to 10 minutes.

[0031] Preferably, the alternation of forward rotation and reverse rotation includes switching from forward rotation to reverse rotation, or switching from reverse rotation to forward rotation.

[0032] Preferably, the preparation method further comprises a pulverization and a tableting performed sequentially before the sintering.

[0033] Preferably, the primary comminution method comprises a vibration mill.

[0034] Preferably, the vibration time of the vibration mill in the primary crushing is 10s to 5min, for example, it can be 10s, 20s, 30s, 40s, 50s, 1min, 2min, 3min, 4min or 5min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 20s to 1min.

[0035] Preferably, the pressure of the primary tableting is 9 MPa to 60 MPa, for example, 9 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa or 60 MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 15 MPa to 30 MPa.

[0036] In the present invention, by limiting the pressure of the first tableting, it is ensured that the particles of the obtained flake material after tableting have good contact with each other; when the pressure of the first tableting is too low, the contact between the particles of the obtained flake material will be poor, thereby resulting in insufficient reaction during the first sintering process; conversely, when the pressure of the first tableting is too high, it not only increases the requirements for the tableting mold, but also causes the obtained flake material to generate greater internal stress, thereby causing the pressed flake material to be delaminated and fragile.

[0037] Preferably, the time for tableting once is 15s to 300s, for example, it can be 15s, 20s, 30s, 40s, 50s, 60s, 80s, 100s, 130s, 150s, 180s, 200s, 250s, 280s or 300s, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 60s to 120s.

[0038] In the present invention, by limiting the time of tableting once, the contact between the particles of the obtained flake material after tableting is good; when the time of tableting once is too short, the flake material will become loose again due to the rebound of force; on the contrary, when the time of tableting once is too long, the tableting time will be too long, thereby reducing the preparation efficiency.

[0039] Preferably, the primary sintering is performed sequentially with a heating and a heat preservation.

[0040] Preferably, the rate of the primary heating is 3°C / min to 5°C / min, for example, 3°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] Preferably, the endpoint temperature of the primary heating is 300°C to 500°C, for example, it may be 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 500°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 300°C to 400°C.

[0042] The end point temperature of the first heating described in the present invention is the temperature of the first insulation. When the temperature of the first insulation is too low, the conductivity of the solid electrolyte will deteriorate, because the sintering temperature is not enough, resulting in the failure to synthesize the target product; when the temperature of the first insulation is too high, the conductivity of the solid electrolyte will decrease, because the sintering temperature is high and other by-products will be generated.

[0043] Preferably, the insulation time is 5h to 12h, for example, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 7h to 9h.

[0044] Preferably, a pressure of 1 MPa to 60 MPa is applied to the mixture during the first heating process, for example, it may be 1 MPa, 2 MPa, 5 MPa, 10 MPa, 15 MPa, 20 MPa, 30 MPa, 40 MPa, 50 MPa or 60 MPa, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably a pressure of 15 MPa to 30 MPa.

[0045] Preferably, the primary sintering atmosphere includes any one of an air atmosphere, an inert atmosphere or a nitrogen atmosphere.

[0046] The primary sintering described in the present invention can be carried out in a muffle furnace, for example. The upper and lower ends of the muffle furnace are equipped with special tungsten carbide pressure rods, which are externally connected to a tablet press to ensure that the pressure is maintained or increased during the firing process; the special tungsten carbide pressure rod can also be made of other materials, such as silicon carbide, boron carbide, boron nitride or silicon nitride.

[0047] Preferably, secondary pulverization and secondary tableting are performed in sequence between the primary sintering and the secondary sintering.

[0048] Preferably, the secondary crushing method includes vibration milling.

[0049] Preferably, the vibration time of the vibration mill in the secondary crushing is 10s to 5min, for example, it can be 10s, 20s, 30s, 40s, 50s, 1min, 2min, 3min, 4min or 5min, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 20s to 1min.

[0050] Preferably, the secondary tableting pressure is 9 MPa to 60 MPa, for example, 9 MPa, 10 MPa, 15 MPa, 20 MPa, 25 MPa, 30 MPa, 35 MPa, 40 MPa, 45 MPa, 50 MPa, 55 MPa or 60 MPa, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 15 MPa to 30 MPa.

[0051] In the present invention, by limiting the pressure of the secondary tableting, it is ensured that the particles of the obtained flake material after tableting have good contact with each other; when the pressure of the secondary tableting is too low, the contact between the particles of the obtained flake material will be poor, resulting in insufficient reaction; on the contrary, when the pressure of the secondary tableting is too high, it not only increases the requirements for the tableting mold, but also causes the obtained flake material to generate greater internal stress, thereby causing the pressed flake material to be layered and fragile.

[0052] Preferably, the time for the secondary tableting is 15s to 300s, for example, it can be 15s, 20s, 30s, 40s, 50s, 60s, 80s, 100s, 130s, 150s, 180s, 200s, 250s, 280s or 300s, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 60s to 120s.

[0053] In the present invention, the contact between the particles of the obtained flake material after tableting is good by limiting the time of the secondary tableting. When the time of the secondary tableting is too short, the flake material will become loose again due to the rebound of the force. On the contrary, when the time of the secondary tableting is too long, the tableting time will be too long, thereby reducing the preparation efficiency.

[0054] The primary sintering described in the present invention can be carried out in a muffle furnace, for example. The upper and lower ends of the muffle furnace are equipped with special tungsten carbide pressure rods, which are externally connected to a tablet press to ensure that the pressure is maintained or increased during the firing process; the special tungsten carbide pressure rod can also be made of other materials, such as silicon carbide, boron carbide, boron nitride or silicon nitride.

[0055] Preferably, the secondary sintering includes secondary heating and secondary heat preservation performed in sequence, the pressure increase is started at the same time as the secondary heating begins, and the pressure preservation is stopped at the same time as the secondary heat preservation ends.

[0056] Preferably, the secondary heating rate is 3°C / min to 5°C / min, for example, it can be 3°C / min, 3.2°C / min, 3.4°C / min, 3.6°C / min, 3.8°C / min, 4°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] Preferably, the endpoint temperature of the secondary heating is 900°C to 1200°C, for example, it can be 900°C, 920°C, 950°C, 970°C, 1000°C, 1020°C, 1050°C, 1070°C, 1100°C, 1120°C, 1150°C, 1170°C or 1200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1050°C to 1150°C.

[0058] The endpoint temperature of the secondary heating in the present invention is the temperature of the secondary insulation. When the temperature of the secondary insulation is too low, the conductivity of the solid electrolyte will become low, because the synthetic product is impure due to the low temperature; when the temperature of the secondary insulation is too high, the conductivity of the solid electrolyte will become low, because the synthetic product is impure due to the high temperature.

[0059] Preferably, the secondary insulation time is 6h to 12h, for example, it can be 6h, 6.5h, 7h, 8h, 9h, 10h, 10.5h, 11h, 11.5h or 12h, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 8h to 10h.

[0060] Preferably, the atmosphere of the secondary sintering includes any one of an air atmosphere, an inert atmosphere or a nitrogen atmosphere.

[0061] As a preferred technical solution of the preparation method of the present invention, the preparation method comprises:

[0062] (1) mixing solid electrolyte raw materials by dry ball milling at a rotation speed of 200 r / min to 500 r / min for 30 min to 1800 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.1 h to h, and the time of each reverse rotation is independently 0.1 h to h; each time the forward rotation and reverse rotation are alternately stopped for 5 min to 15 min;

[0063] (2) the mixture obtained in step (1) is crushed by a vibration mill for 10 seconds to 5 minutes, and then tabletted at a pressure of 9 MPa to 60 MPa for 15 seconds to 300 seconds, and then heated to 300° C. to 500° C. at a rate of 3° C. / min to 5° C. / min under a pressure of 1 MPa to 60 MPa, and then kept warm for 5 hours to 12 hours to obtain a precursor material;

[0064] (3) The precursor material obtained in step (2) is crushed by a vibration mill for 10 seconds to 5 minutes, and then pressed into tablets at a pressure of 9 MPa to 60 MPa for 15 seconds to 300 seconds, and then pressurized and heated at the same time, wherein the heating comprises heating to 900°C to 1200°C at a rate of 3°C / min to 5°C / min and then keeping the temperature for 6 hours to 12 hours, and the pressurizing comprises increasing the pressure to 30 MPa to 45 MPa at a rate of 2 MPa / h to 3 MPa / h and then maintaining the pressure, and the pressure maintenance and heat preservation are terminated at the same time to obtain a solid electrolyte.

[0065] In a second aspect, the present invention provides a solid electrolyte, which is obtained by the preparation method described in the first aspect.

[0066] Preferably, the solid electrolyte includes any one of a NASICON-type solid electrolyte, a garnet-type solid electrolyte or a perovskite-type solid electrolyte.

[0067] Preferably, the density of the solid electrolyte is 92% to 99%, for example, it can be 92%, 93%, 94%, 95%, 96%, 97%, 98% or 99%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] Preferably, the molecular formula of the NASICON solid electrolyte is Na 3 Zr 2 Si 2 PO 12 .

[0069] In a third aspect, the present invention provides a solid-state battery, comprising the solid electrolyte described in the second aspect.

[0070] Compared with the prior art, the present invention has the following beneficial effects:

[0071] The preparation method of the present invention obtains a solid electrolyte with a short grain boundary distance and a moderate grain size by first increasing the pressure of the precursor material and then maintaining the pressure during the secondary sintering process, and effectively reduces the pores generated inside the solid electrolyte, thereby obtaining a high-density solid electrolyte and improving the ionic conductivity of the solid electrolyte. DETAILED DESCRIPTION

[0072] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0073] Example 1

[0074] This embodiment provides a method for preparing a solid electrolyte, the preparation method comprising:

[0075] (1) mixing solid electrolyte raw materials (14.98 g of sodium carbonate, 5.94 g of ammonium dihydrogen phosphate, 23.23 g of zirconium oxide and 11.32 g of silicon oxide) by dry ball milling at a rotation speed of 380 r / min for 180 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; each forward rotation time is 0.5 h, and each reverse rotation time is 0.5 h; each forward rotation and reverse rotation are stopped for 10 min;

[0076] (2) the mixture obtained in step (1) was crushed by a vibration mill for 30 seconds, and then tableted at a pressure of 20 MPa for 120 seconds, and then heated to 400° C. at a rate of 4° C. / min under a pressure of 20 MPa and kept warm for 8 hours to obtain a precursor material;

[0077] (3) The precursor material obtained in step (2) is crushed by a vibration mill for 30 seconds, and then pressed into tablets at a pressure of 20 MPa for 120 seconds. Then, pressurization and heating are started simultaneously. The heating comprises heating to 1150°C at a rate of 4°C / min and then keeping the temperature for 12 hours. The pressurization comprises increasing the pressure to 35 MPa at a rate of 2.5 MPa / h and then maintaining the pressure. The pressure maintenance and heat preservation are ended simultaneously to obtain a solid electrolyte.

[0078] Example 2

[0079] This embodiment provides a method for preparing a solid electrolyte, the preparation method comprising:

[0080] (1) mixing solid electrolyte raw materials (23.75 g of sodium bicarbonate, 6.69 g of phosphorus pentoxide, 23.23 g of zirconium oxide and 11.32 g of silicon oxide) by dry ball milling at a rotation speed of 300 r / min for 1500 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.3 h, and the time of each reverse rotation is independently 0.8 h; and the forward rotation and reverse rotation are stopped for 9 minutes each time they are alternated;

[0081] (2) the mixture obtained in step (1) was crushed by a vibration mill for 20 seconds, and then tableted at a pressure of 30 MPa for 60 seconds, and then heated to 340° C. at a rate of 3.5° C. / min at a pressure of 30 MPa and kept warm for 9 hours to obtain a precursor material;

[0082] (3) The precursor material obtained in step (2) is crushed by a vibration mill for 1 minute and then pressed into tablets at a pressure of 15 MPa for 300 seconds. Pressing and heating are then started simultaneously. The heating comprises heating to 1050°C at a rate of 3.5°C / min and then keeping the temperature for 10 hours. The pressurizing comprises increasing the pressure to 32 MPa at a rate of 2.2 MPa / h and then maintaining the pressure. The pressure maintenance and heat preservation are ended simultaneously to obtain a solid electrolyte.

[0083] Example 3

[0084] This embodiment provides a method for preparing a solid electrolyte, the preparation method comprising:

[0085] (1) mixing solid electrolyte raw materials (14.98 g of sodium carbonate, 6.69 g of phosphorus pentoxide, 23.23 g of zirconium oxide and 11.32 g of silicon oxide) by dry ball milling at a rotation speed of 480 r / min for 120 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.8 h, and the time of each reverse rotation is independently 0.3 h; and the forward rotation and reverse rotation are stopped for 7 min each time;

[0086] (2) the mixture obtained in step (1) was crushed by a vibration mill for 1 min, and then tableted at a pressure of 15 MPa for 100 s, and then heated to 380° C. at a rate of 4.5° C. / min at a pressure of 15 MPa and kept warm for 7 h to obtain a precursor material;

[0087] (3) The precursor material obtained in step (2) is crushed by a vibration mill for 20 seconds, and then pressed into tablets at a pressure of 30 MPa for 60 seconds, and then pressurized and heated simultaneously. The heating includes heating to 1100°C at a rate of 4.5°C / min and then keeping the temperature for 8 hours. The pressurization includes increasing the pressure to 40 MPa at a rate of 2.8 MPa / h and then maintaining the pressure. The pressure maintenance and heat preservation are terminated simultaneously to obtain a solid electrolyte.

[0088] Example 4

[0089] This embodiment provides a method for preparing a solid electrolyte, the preparation method comprising:

[0090] (1) mixing solid electrolyte raw materials (23.75 g of sodium bicarbonate, 5.94 g of ammonium dihydrogen phosphate, 23.23 g of zirconium oxide and 11.32 g of silicon oxide) by dry ball milling at a rotation speed of 200 r / min for 1800 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 1 hour, and the time of each reverse rotation is independently 1 hour; and the forward rotation and reverse rotation are stopped for 15 minutes each time they are alternated;

[0091] (2) the mixture obtained in step (1) was crushed by a vibration mill for 5 minutes, and then tableted at a pressure of 9 MPa for 300 seconds, and then heated to 300° C. at a rate of 3° C. / min under a pressure of 1 MPa and kept warm for 12 hours to obtain a precursor material;

[0092] (3) The precursor material obtained in step (2) is crushed by a vibration mill for 10 seconds, and then pressed into tablets at a pressure of 60 MPa for 15 seconds, and then pressurized and heated simultaneously. The heating includes heating to 1200°C at a rate of 5°C / min and then keeping the temperature for 6 hours. The pressurization includes increasing the pressure to 45 MPa at a rate of 3 MPa / h and then maintaining the pressure. The pressure maintenance and heat preservation are terminated simultaneously to obtain a solid electrolyte.

[0093] Example 5

[0094] This embodiment provides a method for preparing a solid electrolyte, the preparation method comprising:

[0095] (1) mixing solid electrolyte raw materials (14.98 g of sodium carbonate, 6.03 g of diammonium hydrogen phosphate, 23.23 g of zirconium oxide and 11.32 g of silicon oxide) by dry ball milling at a rotation speed of 500 r / min for 30 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.1 h, and the time of each reverse rotation is independently 0.1 h; and the forward rotation and reverse rotation are stopped for 5 min each time;

[0096] (2) the mixture obtained in step (1) was crushed by a vibration mill for 10 seconds, and then tableted at a pressure of 60 MPa for 15 seconds, and then heated to 500° C. at a rate of 5° C. / min under a pressure of 60 MPa and kept warm for 5 hours to obtain a precursor material;

[0097] (3) The precursor material obtained in step (2) is crushed by a vibration mill for 5 minutes, and then pressed into tablets at a pressure of 9 MPa for 90 seconds. Then, pressurization and heating are started simultaneously. The heating includes heating to 900°C at a rate of 3°C / min and then keeping the temperature for 9 hours. The pressurization includes increasing the pressure to 30 MPa at a rate of 2 MPa / h and then maintaining the pressure. The pressure maintenance and heat preservation are ended simultaneously to obtain a solid electrolyte.

[0098] Example 6

[0099] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the rotation speed of the dry ball milling in step (1) is 100 r / min.

[0100] Example 7

[0101] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the rotation speed of the dry ball milling in step (1) is 600 r / min.

[0102] Example 8

[0103] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the dry ball milling time in step (1) is 20 minutes.

[0104] Example 9

[0105] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the dry ball milling time in step (1) is 2000 min.

[0106] Example 10

[0107] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that in step (2), the obtained mixture is crushed by a vibration mill and then tabletted at a pressure of 5 MPa.

[0108] Embodiment 11

[0109] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that in step (2), the obtained mixture is crushed by a vibration mill and then tabletted for 10 seconds.

[0110] Example 12

[0111] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the temperature is raised to 200° C. and then kept warm in step (2).

[0112] Embodiment 13

[0113] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the temperature is raised to 600° C. and then kept warm in step (2).

[0114] Embodiment 14

[0115] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that in step (3), the obtained mixture is crushed by a vibration mill and then pressed into tablets at a pressure of 5 MPa.

[0116] Embodiment 15

[0117] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that in step (3), the obtained precursor material is crushed by a vibration mill and then tabletted for 10 seconds.

[0118] Example 16

[0119] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the temperature is raised to 700° C. and then kept warm in step (3).

[0120] Embodiment 17

[0121] This embodiment provides a method for preparing a solid electrolyte, which is the same as that of Embodiment 1 except that the temperature is raised to 1400° C. and then kept warm in step (3).

[0122] Comparative Example 1

[0123] This comparative example provides a method for preparing a solid electrolyte, which is the same as Example 1 except that the pressurization rate in step (3) is 1 MPa / h.

[0124] Comparative Example 2

[0125] This comparative example provides a method for preparing a solid electrolyte, which is the same as Example 1 except that the pressurization rate in step (3) is 5 MPa / h.

[0126] Comparative Example 3

[0127] This comparative example provides a method for preparing a solid electrolyte, which is the same as Example 1 except that the pressure is increased to 25 MPa and then maintained in step (3).

[0128] Comparative Example 4

[0129] This comparative example provides a method for preparing a solid electrolyte, which is the same as Example 1 except that the entire pressurization step described in step (3) is omitted.

[0130] The solid electrolyte prepared by the preparation method provided in the above embodiments and comparative examples was tested for electrical conductivity. The testing method is as follows: an electrochemical workstation is used, a blocking battery mold is used, and after the prepared solid electrolyte is assembled at room temperature, an AC impedance test is performed. The calculated electrical conductivity is shown in Table 1; wherein, the calculation formula for electrical conductivity calculation is: σ=(L / S)×R, σ represents ionic conductivity, L is the thickness of the electrolyte sheet, S is the area of ​​the electrolyte sheet, and R is the impedance value measured by the electrolyte sheet.

[0131] Table 1

[0132]

[0133]

[0134] From Table 1, we can get:

[0135] (1) The steps of the preparation methods provided in Examples 1 to 5 of the present invention are simple and easy to implement, and the prepared solid electrolyte has a high electrical conductivity.

[0136] (2) By comparing Example 1 with Examples 6 and 7, it can be seen that the rotation speed of the dry ball milling in the present invention affects the performance of the prepared solid electrolyte; when the rotation speed of the dry ball milling is too low, the conductivity of the solid electrolyte will be reduced, because the dry ball milling rate is too low, which will cause uneven mixing of the raw materials and more impurities in the reaction product; when the rotation speed of the dry ball milling is too fast, the conductivity of the solid electrolyte will be reduced, because when the dry ball milling rate is too high, the powder material will be agglomerated at the bottom of the ball mill due to the high rotation speed, resulting in uneven mixing of the raw materials;

[0137] (3) By comparing Example 1 with Examples 8 and 9, it can be seen that the dry ball milling time in the present invention affects the performance of the prepared solid electrolyte; when the dry ball milling time is too short, the conductivity of the solid electrolyte will be reduced, because when the dry ball milling time is too short, the particle size of the obtained mixture will be not fine enough and the mixing will be uneven; when the dry ball milling time is too long, the conductivity of the solid electrolyte will be reduced, because the ball milling tank and the ball milling beads will be worn and fall off, thereby contaminating the sample;

[0138] (4) By comparing Example 1 with Example 10, it can be seen that the pressure of the first tablet pressing in the present invention affects the performance of the prepared solid electrolyte; when the pressure of the first tablet pressing is too small, the conductivity of the solid electrolyte will become lower. This is because when the pressure of the first tablet pressing is too low, the contact between the obtained flake material particles will be poor, resulting in insufficient reaction during the first sintering process;

[0139] (5) By comparing Example 1 with Example 11, it can be seen that the time of a tableting operation in the present invention affects the performance of the prepared solid electrolyte; when the time of a tableting operation is too short, the conductivity of the solid electrolyte will be reduced. This is because when the time of a tableting operation is too short, the sheet material will become loose again due to the rebound of the force;

[0140] (6) By comparing Example 1 with Examples 12 and 13, it can be seen that the temperature of the first insulation in the first sintering in the present invention affects the performance of the prepared solid electrolyte; when the temperature of the first insulation is too low, the conductivity of the solid electrolyte will deteriorate, which is because the sintering temperature is not enough and the target product cannot be synthesized; when the temperature of the first insulation is too high, the conductivity of the solid electrolyte will decrease, which is because the sintering temperature is high and other by-products will be generated;

[0141] (7) By comparing Example 1 with Example 14, it can be seen that the pressure of the secondary tableting in the present invention affects the performance of the prepared solid electrolyte; when the pressure of the secondary tableting is too small, the conductivity of the solid electrolyte will become lower. This is because when the pressure of the secondary tableting is too low, the contact between the obtained sheet material particles will be poor, resulting in insufficient reaction;

[0142] (8) By comparing Example 1 with Example 15, it can be seen that the time of secondary tableting in the present invention affects the performance of the prepared solid electrolyte; when the time of secondary tableting is too short, the conductivity of the solid electrolyte will be reduced. This is because when the time of secondary tableting is too short, the sheet material will become loose again due to the rebound of the force;

[0143] (9) By comparing Example 1 with Examples 16 and 17, it can be seen that the temperature of the secondary insulation in the secondary sintering in the present invention affects the performance of the prepared solid electrolyte; when the temperature of the secondary insulation is too low, the conductivity of the solid electrolyte will be reduced, which is because the synthetic product is impure due to the low temperature; when the temperature of the secondary insulation is too high, the conductivity of the solid electrolyte will be reduced, which is because the synthetic product is impure due to the high temperature;

[0144] (10) By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the pressure increase rate in the pressurization described in the present invention affects the performance of the prepared solid electrolyte; when the pressure increase rate is too slow, the conductivity of the solid electrolyte will be reduced. This is because the pressure increase rate is too slow, resulting in poor contact between particles during the sintering process, resulting in insufficient reaction; when the pressure increase rate is too fast, the conductivity of the solid electrolyte will be reduced. This is because the electrolyte sheet is not pressed evenly enough, resulting in low density;

[0145] (11) By comparing Example 1 with Comparative Example 3, it can be seen that the end pressure of the pressurization in the present invention, that is, the pressure of the pressure maintenance, will affect the performance of the prepared solid electrolyte; when the pressure of the pressure maintenance is too low, the conductivity of the solid electrolyte will become low, because the density of the fired electrolyte sheet is not enough due to the low pressure;

[0146] (12) By comparing Example 1 with Comparative Example 4, it can be seen that the preparation method of the present invention obtains a high-density solid electrolyte by first increasing the pressure of the precursor material and then maintaining the pressure during the secondary sintering process, thereby improving the ionic conductivity of the solid electrolyte.

[0147] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a solid electrolyte, characterized in that: The preparation method comprises: The mixture of solid electrolyte raw materials is subjected to primary sintering to obtain a precursor material, and the obtained precursor material is subjected to secondary sintering to obtain a solid electrolyte; The secondary sintering process includes pressurizing the precursor material, and the pressurization includes increasing the pressure to 30MPa-45MPa at a pressure increase rate of 2MPa / h-3MPa / h and then maintaining the pressure.

2. The preparation method according to claim 1, characterized in that: The solid electrolyte raw materials include inorganic salts and oxides; Preferably, the inorganic salt includes any one of sodium carbonate, sodium bicarbonate, ammonium hydrogen phosphate or ammonium dihydrogen phosphate, or a combination of at least two thereof; the oxide includes any one of phosphorus pentoxide, phosphorus trioxide, zirconium dioxide or silicon dioxide, or a combination of at least two thereof; Preferably, the method of preparing the mixture comprises mixing the solid electrolyte raw materials by dry ball milling; Preferably, the rotation speed of the dry ball mill is 200 r / min to 500 r / min, preferably 300 r / min to 480 r / min; Preferably, the dry ball milling time is 30 min to 1800 min, preferably 120 min to 1500 min; Preferably, the forward rotation and the reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.1h to 1h, and the time of each reverse rotation is independently 0.1h to 1h; each time the forward rotation and the reverse rotation are alternately stopped for 5min to 15min, preferably 5min to 10min.

3. The preparation method according to claim 1 or 2, characterized in that: The preparation method further comprises a crushing and a tabletting process performed sequentially before the sintering; Preferably, the primary comminution method includes a vibration mill; Preferably, the vibration time of the vibration mill in the primary pulverization is 10s to 5min, preferably 20s to 1min; Preferably, the pressure of the primary tableting is 9MPa to 60MPa, preferably 15MPa to 30MPa; Preferably, the time for tableting once is 15s to 300s, preferably 60s to 120s.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The primary sintering is performed sequentially with a heating and a heat preservation; Preferably, the rate of the primary heating is 3°C / min to 5°C / min; Preferably, the end temperature of the first heating is 300°C to 500°C, preferably 300°C to 400°C; Preferably, the time of the first insulation is 5h to 12h, preferably 7h to 9h; Preferably, a pressure of 1 MPa to 60 MPa, preferably 15 MPa to 30 MPa, is applied to the mixture during the first heating process.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The first sintering and the second sintering also include the second crushing and the second tableting performed in sequence; Preferably, the secondary crushing method includes vibration mill; Preferably, the vibration time of the vibration mill in the secondary crushing is 10s to 5min, preferably 20s to 1min; Preferably, the secondary tableting pressure is 9MPa to 60MPa, preferably 15MPa to 30MPa; Preferably, the secondary tableting time is 15s to 300s, preferably 60s to 120s.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The secondary sintering includes secondary heating and secondary heat preservation in sequence, the pressure increase starts at the same time as the secondary heating starts, and the pressure preservation stops at the same time as the secondary heat preservation ends; Preferably, the secondary heating rate is 3°C / min to 5°C / min; Preferably, the end temperature of the secondary heating is 900°C to 1200°C, preferably 1050°C to 1150°C; Preferably, the secondary insulation time is 6 h to 12 h, preferably 8 h to 10 h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises: (1) mixing solid electrolyte raw materials by dry ball milling at a rotation speed of 200 r / min to 500 r / min for 30 min to 1800 min to obtain a mixture of solid electrolyte raw materials, wherein forward rotation and reverse rotation are performed alternately in the dry ball milling; the time of each forward rotation is independently 0.1 h to 1 h, and the time of each reverse rotation is independently 0.1 h to 1 h; and the forward rotation and reverse rotation are stopped for 5 min to 15 min each time; (2) the mixture obtained in step (1) is crushed by a vibration mill for 10 seconds to 5 minutes, and then tabletted at a pressure of 9 MPa to 60 MPa for 15 seconds to 300 seconds, and then heated to 300° C. to 500° C. at a rate of 3° C. / min to 5° C. / min under a pressure of 1 MPa to 60 MPa, and then kept warm for 5 hours to 12 hours to obtain a precursor material; (3) The precursor material obtained in step (2) is crushed by a vibration mill for 10 seconds to 5 minutes, and then pressed into tablets at a pressure of 9 MPa to 60 MPa for 15 seconds to 300 seconds, and then pressurized and heated at the same time, wherein the heating comprises heating to 900°C to 1200°C at a rate of 3°C / min to 5°C / min and then keeping the temperature for 6 hours to 12 hours, and the pressurizing comprises increasing the pressure to 30 MPa to 45 MPa at a rate of 2 MPa / h to 3 MPa / h and then maintaining the pressure, and the pressure maintenance and heat preservation are terminated at the same time to obtain a solid electrolyte.

8. A solid electrolyte, characterized in that The solid electrolyte is obtained by the preparation method according to any one of claims 1 to 7.

9. The solid electrolyte according to claim 8, characterized in that The solid electrolyte includes any one of a NASICON solid electrolyte, a garnet solid electrolyte or a perovskite solid electrolyte; Preferably, the density of the solid electrolyte is 92% to 99%; Preferably, the molecular formula of the NASICON solid electrolyte is Na3Zr2Si2PO 12 .

10. A solid-state battery, characterized in that: The solid-state battery comprises the solid electrolyte according to claim 8 or 9.

Citation Information

Patent Citations

  • Preparation method of ion-doped germanium lithium phosphate-based solid electrolyte

    CN105762414A